The intermediate polar cataclysmic variable GK Persei 120 years after the nova explosion: a first dynamical mass study. Issue 4 (10th September 2021) - Álvarez-Hernández, A; Torres, M A P; Rodríguez-Gil, P; Shahbaz, T; Anupama, G C; Gazeas, K D; Pavana, M; Raj, A; Hakala, P; Stone, G; Gomez, S; Jonker, P G; et al.
ABSTRACT: We present a dynamical study of the intermediate polar and dwarf nova cataclysmic variable GK Persei (Nova Persei 1901) based on a multisite optical spectroscopy and R -band photometry campaign. The radial velocity curve of the evolved donor star has a semi-amplitude K_2=126.4 ± 0.9 km s^-1 and an orbital period P=1.996872 ± 0.000009 d . We refine the projected rotational velocity of the donor star to v_rot i = 52 ± 2 km s^-1 that, together with K 2, provides a donor star to white dwarf mass ratio q = M 2 / M 1 = 0.38 ± 0.03. We also determine the orbital inclination of the system by modelling the phase-folded ellipsoidal light curve and obtain i = 67° ± 5°. The resulting dynamical masses are M_1=1.03^+0.16_-0.11 M_ and M_2 = 0.39^+0.07_-0.06 M_ at 68 per cent confidence level. The white dwarf dynamical mass is compared with estimates obtained by modelling the decline light curve of the 1901 nova event and X-ray spectroscopy. The best matching mass estimates come from the nova light curve models and an X-ray data analysis that uses the ratio between the Alfvén radius in quiescence and during dwarf nova outburst.